CLINICAL FEATURES OF A CHRONIC BACTERIAL PROSTATITIS AGAINST DEFICIENCY OF TESTOSTERONE - H. S. Ibishev; A. A. Chernyj; M. I. Kogan (Вестник урологии, 2013)
The study involved 124 patients aged 20-45 years with a diagnosis of chronic bacterial prostatitis. In 37% of patients with chronic bacterial prostatitis testosterone was below the standard indicators. The study revealed that the majority of patients with chronic bacterial prostatitis, with a deficit of general clinical picture of Tc addition to pain presented various forms of sexual dysfunction, as well as lower urinary tract symptoms. In assessing the clinical performance more pronounced changes were observed in patients with decreased testosterone levels in comparison with patients with normal testosterone levels.